Penerapan Metode Bermain Peran Mikro untuk Meningkatkan Kemampuan Berbicara Anak Usia 5-6 Tahun Di TK Negeri Pembina Mataram Tahun Ajaran 2019/2020 - Lisharti Lisharti; Fahruddin Fahruddin; Nurhasanah Nurhasanah (Indonesian Journal of Elementary and Childhood Education, 2020)
Speaking ability is a person's effort to communicate ideas, thoughts, or feelings, to misrepresent an information to others using articulation sounds or verbal words. The purpose of this study is the application of micro role-playing method to improve the ability to speak children aged 5-6 years in TK Negeri Pembina Mataram. This method of research is development research, with three stages of development that each study consists of planning, implementation, observation, and evaluation stages. The subject in this study was a child aged 5-6 years B3, numbering 15 children. Methods of collecting data are observation methods. Data analysis uses qualitative descriptive analysis. The application of micro role play method is done with several stages namely, 1). Preparation, the teacher determines the theme, prepares the play tool, introduces the playing tool, and organizes the venue's main activities. 2). Initial activity, the teacher explains the technique of play, makes the rules, and the child selects the role that has been specified. 3). Core activities, children play in groups, teachers supervise the child, remind the time of play will soon end and settle the hangout with the child. 4). The final activity, the child tells the playing experience, and the teacher gives the child a compliment. The results of the study of the implementation of micro-role play method showed that the average children's speech increased ability is on development I 53.78%, then in development II 71.89%, and development III 88.78%. In conclusion, that the application of micro-role play method can improve the ability to speak children aged 5-6 years in TK Negeri Pembina Mataram. Development of children's speaking skills can be increased using micro-role play methods that are carried out repeatedly by making improvements at each stage of development.